2018
DOI: 10.18388/abp.2017_1613
|View full text |Cite
|
Sign up to set email alerts
|

The role of MGMT polymorphisms (Rs12917 and Rs11016879) in head and neck cancer risk and prognosis

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the leading cancers by incidence worldwide. The risk of these cancers is strictly associated with alkylation factors present in tobacco smoke. The crucial role in preventing DNA alkylation is played by O-methylguanine-DNA methyltransferase (MGMT). Dysfunction or lack of MGMT is associated with an increased risk of cancer. The aim of the study was to assess the influence of MGMT polymorphisms: rs12917 and rs11016879 on HNSCC risk and course. The study cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In 2010, Zhong et al [12] performed the first meta-analysis on this topic, reviewing 28 case–control studies from 26 articles [4,5,20,22,23,26–28,31,33–35,37,38,42,45,49,51,52,54,55,59–63]. Another 24 case–control studies [16–19,21,24,25,29,30,32,36,39–41,43,44,46–48,50,53,56–58] were included in our study. We excluded three studies not in-line with the HWE principle [61–63] and one that focussed only on colorectal adenomatous or hyperplastic polyps but not on colorectal cancer [60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2010, Zhong et al [12] performed the first meta-analysis on this topic, reviewing 28 case–control studies from 26 articles [4,5,20,22,23,26–28,31,33–35,37,38,42,45,49,51,52,54,55,59–63]. Another 24 case–control studies [16–19,21,24,25,29,30,32,36,39–41,43,44,46–48,50,53,56–58] were included in our study. We excluded three studies not in-line with the HWE principle [61–63] and one that focussed only on colorectal adenomatous or hyperplastic polyps but not on colorectal cancer [60].…”
Section: Discussionmentioning
confidence: 99%
“…We excluded one of these studies [64] from our meta-analysis because it did not meet the requirement of full genotype frequency in both case and control groups. Finally, we enrolled another ten case–control studies [4,21,25,29,30,35,36,42,45,48]. In addition, when compared with another meta-analysis of Liu et al (2013) [13], which consisted of 44 case–control studies from 37 articles [4,5,16,17,19,20,22,23,25–27,31–33,35,37,38,42,43,45–47,49,51,52,54–63,65,66], we excluded four studies that were not in HWE [61–63,66], one that did not analyze colorectal cancer [60], and one that included other genetic variants [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, this polymorphism is also associated with a reduced risk of endometrial cancers (Sharma et al ., 2009). Even more peculiarly, studies exist for both increased and reduced risk of head and neck carcinomas in subjects carrying rs12917 SNP (Kiczmer et al ., 2018). In similar, while some studies showed no effect of this SNP on lung cancer risk, some other studies showed a risk-increasing effect of this allele (Martínez-Ramírez et al ., 2019; Sharma et al ., 2019).…”
Section: Mgmt Snp’s In Carcinogenesis Tmz Myelotoxicity and Tumoral R...mentioning
confidence: 99%
“…However, not all individuals with these risk factors will eventually develop HNC, which indicates that genetic factors may play a critical role in the carcinogenesis and progression of HNC. Cumulative evidence indicates that genetic variants contribute to the risk of HNC [6][7][8]. However, a large number of risk polymorphisms associated with HNC predisposition have not been discovered.…”
Section: Introductionmentioning
confidence: 99%